2014
DOI: 10.1080/19455224.2014.931872
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of long term storage solutions for rubber garments

Abstract: A collection of 1980s Mexican rubberised cotton garments was investigated in order to assess conservation treatment options, to improve their long term storage conditions and to investigate the origin of the strong odour associated with the garments. Chemical and mechanical deterioration of the rubber was confirmed by FTIR and SEM analyses. Recommendations for remedial conservation were made after trials to re-shape a garment by the application of gentle heat. Passive diffusion tube sampling was carried out to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Coated piezo-electric quartz crystals ( pqc) have also been investigated as an alternative method of measurement of damage to specific materials from volatiles and other environmental factors (Odlyha et al, 2011). It has been observed that A-D (acid-detector) strips give a useful and quick visual guide to expected levels of volatile acids (Fenn, 1995;Hacke et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Coated piezo-electric quartz crystals ( pqc) have also been investigated as an alternative method of measurement of damage to specific materials from volatiles and other environmental factors (Odlyha et al, 2011). It has been observed that A-D (acid-detector) strips give a useful and quick visual guide to expected levels of volatile acids (Fenn, 1995;Hacke et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The cardboard and rubber elements are particularly oxygen-sensitive, and tend to delaminate, crumble, crack, and discolor. Special energy and material intensive storage conditions will retard decomposition (Dyer et al, 2011;Hacke et al, 2014;Shashoua, 1999). Photograph courtesy of the Robert Rauschenberg Foundation.…”
Section: Notable Uses Of Anoxia For Cultural Heritage In the United S...mentioning
confidence: 99%
“…Cultural heritage and historic collections frequently contain objects that require insect eradication or long-term storage under anoxic (low oxygen) conditions. Optimal anoxic treatments involve placing the object(s) in sealed, oxygen-impermeable enclosures, reducing the oxygen content to less than 1%, and maintaining the anoxic environment for a given period (Hacke et al, 2014;Shashoua, 1999;Trafford & Allington-Jones, 2017) establish an anoxic environment, preservationists decrease the oxygen concentration within an enclosure (constructed from plastic sheets and PVC tubing) by purging it with nitrogen or argon gas or by adding a scavenging agent that binds with oxygen such as zero-valent iron, which is the main component of the commercial oxygen scavenger Ageless ® . To account for potential enclosure leakage, the anoxic environment is maintained with a flow of the purging gas as needed, or with sufficient oxygen scavenger (Shashoua, 1999).…”
Section: Introductionmentioning
confidence: 99%